Afforestation on agricultural land in England: Applying the Theoretical Domains Framework and Behaviour Change Wheel to identify the enablers of change within farmer behaviour - J. Urquhart; A. Goodenough; P.L. Staddon; J. Mills; J. Powell; M. Vigani; P. Simmonds (Journal of Rural Studies, 2025)

Best practices for producing actionable knowledge to inform fisheries management and conservation - Cosette Arseneault-Deraps; Raegan Davis; M. E. Cole MacLeod; Erin Wilson; Ben Aubrey; Alyssa Goodenough; Jamie C. Madden; Kevin A. Adeli; Christopher Cvitanovic; Nathan Young; Julie M. Hinderer; Elizabeth A. Nyboer; et al. (Environmental Biology of Fishes, 2025)

Using a socially-engaged arts approach to exploring how diverse socio-cultural groups accessed, valued, engaged with and benefited from an urban treescape during the COVID-19 Pandemic - A. Goodenough; J. Urquhart; K. Morrison; J.E. Black; P. Courtney; C. Potter (Urban Forestry & Urban Greening, 2024)

A phlogopite-bearing lithospheric mantle source for Europe's largest REE-HFSE belt: Gardar Rift, SW Greenland - Charles D. Beard; Adrian A. Finch; Anouk M. Borst; Kathryn M. Goodenough; William Hutchison; Ian L. Millar; Tom Andersen; Helen M. Williams; Owen M. Weller (Earth and Planetary Science Letters, 2024)

Temperature synchronizes temporal variation in laying dates across European hole‐nesting passerines - Stefan J. G. Vriend; Vidar Grøtan; Marlène Gamelon; Frank Adriaensen; Markus P. Ahola; Elena Álvarez; Liam D. Bailey; Emilio Barba; Jean‐Charles Bouvier; Malcolm D. Burgess; Andrey Bushuev; Carlos Camacho; et al. (Ecology, 2023)
Identifying the environmental drivers of variation in fitness‐related traits is a central objective in ecology and evolutionary biology. Temporal fluctuations of these environmental drivers are often synchronized at large spatial scales. Yet, whether synchronous environmental conditions can generate spatial synchrony in fitness‐related trait values (i.e., correlated temporal trait fluctuations across populations) is poorly understood. Using data from long‐term monitored populations of blue tits ( Cyanistes caeruleus , n = 31), great tits ( Parus major , n = 35), and pied flycatchers ( Ficedula hypoleuca , n = 20) across Europe, we assessed the influence of two local climatic variables (mean temperature and mean precipitation in February–May) on spatial synchrony in three fitness‐related traits: laying date, clutch size, and fledgling number. We found a high degree of spatial synchrony in laying date but a lower degree in clutch size and fledgling number for each species. Temperature strongly influenced spatial synchrony in laying date for resident blue tits and great tits but not for migratory pied flycatchers. This is a relevant finding in the context of environmental impacts on populations because spatial synchrony in fitness‐related trait values among populations may influence fluctuations in vital rates or population abundances. If environmentally induced spatial synchrony in fitness‐related traits increases the spatial synchrony in vital rates or population abundances, this will ultimately increase the risk of extinction for populations and species. Assessing how environmental conditions influence spatiotemporal variation in trait values improves our mechanistic understanding of environmental impacts on populations.

Erratum to: Carbonatites and Alkaline Igneous Rocks in Post-Collisional Settings: Storehouses of Rare Earth Elements - Kathryn M. Goodenough; Eimear A. Deady; Charles D. Beard; Sam Broom-Fendley; Holly A. L. Elliott; Frederick van den Berg; Hüseyin Öztürk (Journal of Earth Science, 2022)

Carbonatites and Alkaline Igneous Rocks in Post-Collisional Settings: Storehouses of Rare Earth Elements - Kathryn M. Goodenough; Eimear A. Deady; Charles D. Beard; Sam Broom-Fendley; Holly A. L. Elliott; Frederick van den Berg; Hüseyin Öztürk (Journal of Earth Science, 2021)
The rare earth elements (REE) are critical raw materials for much of modern technology, particularly renewable energy infrastructure and electric vehicles that are vital for the energy transition. Many of the world’s largest REE deposits occur in alkaline rocks and carbonatites, which are found in intracontinental, rift-related settings, and also in syn- to post-collisional settings. Post-collisional settings host significant REE deposits, such as those of the Mianning-Dechang belt in China. This paper reviews REE mineralization in syn- to post-collisional alkaline-carbonatite complexes worldwide, in order to demonstrate some of the key physical and chemical features of these deposits. We use three examples, in Scotland, Namibia, and Turkey, to illustrate the structure of these systems. We review published geochemical data and use these to build up a broad model for the REE mineral system in post-collisional alkaline-carbonatite complexes. It is evident that immiscibility of carbonate-rich magmas and fluids plays an important part in generating mineralization in these settings, with REE, Ba and F partitioning into the carbonate-rich phase. The most significant REE mineralization in post-collisional alkaline-carbonatite complexes occurs in shallow-level, carbothermal or carbonatite intrusions, but deeper carbonatite bodies and associated alteration zones may also have REE enrichment.

Double-edged effect? Impact of dual edge proximity on the distribution of ancient woodland indicator plant species in a fragmented habitat - K. A. Swallow; A. E. Goodenough (Community Ecology, 2017)

How robust are community-based plant bioindicators? Empirical testing of the relationship between Ellenberg values and direct environmental measures in woodland communities - W. Carpenter; A. Goodenough (Community Ecology, 2014)

Enrichment of Rare Earth Elements during magmatic and post-magmatic processes: a case study from the Loch Loyal Syenite Complex, northern Scotland - A. S. Walters; K. M. Goodenough; H. S. R. Hughes; N. M. W. Roberts; A. G. Gunn; J. Rushton; A. Lacinska (Contributions to Mineralogy and Petrology, 2013)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Are the ecological impacts of alien species misrepresented? A review of the “native good, alien bad” philosophy - A. Goodenough (Community Ecology, 2010)

Fruiting of Agaricus bisporus - D. A. Wood; P. W. Goodenough (Archives of Microbiology, 1977)